Psychological capital moderating the relationship between self-criticism and job satisfaction. - Chia, Camy Yi Zhen. (2011)
This paper explores a potential link between self-criticism and job satisfaction among Asians. Additionally, with the increasing popularity with positive organizational behavior, a recently developed higher-order construct – Psychological Capital (PsyCap)– was hypothesized to act as a moderator for the above-mentioned relationship. This paper further investigated whether PsyCap was a better moderator for the relationship between comparative self-criticism and job satisfaction as compared to internalized self-criticism and job satisfaction. Though results supported the relationship between self-criticism and job satisfaction, the proposed moderating relations were not. Some recommendations were also suggested to improve the methodology for future research.